Population Pharmacokinetic and Exposure–dizziness Modeling for a Metabotropic Glutamate Receptor Subtype 5 Negative Allosteric Modulator in Major Depressive Disorder Patients. Issue 5 (27th June 2018) - Cosson, Valérie; Schaedeli‐Stark, Franziska; Arab‐Alameddine, Mona; Chavanne, Clarisse; Guerini, Elena; Derks, Michael; Mallalieu, Navita L.
Abstract: Dizziness, the most frequently observed adverse event in patients with major depressive disorder, was observed with basimglurant, a selective, orally active metabotropic glutamate receptor subtype 5 negative allosteric modulator. The potential relationship between dizziness and basimglurant exposure was explored. The pharmacokinetics of basimglurant was characterized with nonlinear mixed effects modeling using data from 288 trial participants enrolled in five clinical trials. The pharmacokinetics of basimglurant after daily oral administration of a modified release formulation was best described by a two‐compartment disposition model with a transit compartment, lag time for the absorption, and first‐order elimination. The largest covariate effects were the effect of smoking and male gender on apparent clearance followed by the effect of body weight on distribution volumes. Clearance was twofold higher in smokers and 40% higher in males. A logistic regression model showed a statistically significant correlation between basimglurant Cmax and incidence of dizziness. An increased risk of dizziness is predicted with increasing doses.